Estimations of water balance after validating and administering the water balance questionnaire in pregnant women. (May 2014) - Malisova, Olga; Protopappas, Athanasios; Nyktari, Anastasia; Bountziouka, Vassiliki; Antsaklis, Aristides; Zampelas, Antonis; Kapsokefalou, Maria
Abstract Dehydration during pregnancy may be harmful for the mother and fetus; thus our objective was to understand whether pregnant women balance water intake and loss. The Water Balance Questionnaire (WBQ) was modified to reflect pregnancy (WBQ-P). Validation was performed using 3-day diaries (n = 60) and hydration indices in urine (osmolality, specific gravity, pH and color, n = 40). The WBQ-P was found valid according to Kedhal τ-b coefficient agreement. The WBQ-P was administered to 95, 100 and 97 women per trimester, in Greece. Median (IQR) water balance, intake and loss were, respectively, 203 (−577, 971), 2917 (2187, 3544) and 2658 (2078, 3391) ml/day; these did not differ among the trimesters or between pregnant and non-pregnant women. However, more pregnant women were falling in the higher quartiles of water balance distribution. No differences in sources of water intake were identified except that women in the third trimester had lower water intake from beverages.